2020
DOI: 10.1002/aenm.202000563
|View full text |Cite
|
Sign up to set email alerts
|

An Antiaging Electrolyte Additive for High‐Energy‐Density Lithium‐Ion Batteries

Abstract: critical challenges to be overcome for the successful utilization of Li-rich cathodes in LIBs. Li-rich cathodes suffer from severe voltage decay and continued capacity fading upon repeated cycling mainly because of two unfavorable reactions: 1) the interfacial degradation that stems from an unstable cathode-electrolyte interphase and 2) the irreversible phase transformation from layered to spinel. [9][10][11] Undesirable electrolyte decomposition at the Li-rich cathode with a high operation voltage of 4.4 V ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 59 publications
0
42
0
Order By: Relevance
“…(B, C) Schematic representation of the degradation of a Li-rich cathode by reactive species and protection of a Li-rich cathode by the MA-C 60 additive as a reactive species scavenger and interface modifier. Adapted with permission from ref . Copyright 2020 Wiley-VCH.…”
Section: Challenges and Possible Solutions Of Li-rich Mn-based Oxide ...mentioning
confidence: 99%
See 1 more Smart Citation
“…(B, C) Schematic representation of the degradation of a Li-rich cathode by reactive species and protection of a Li-rich cathode by the MA-C 60 additive as a reactive species scavenger and interface modifier. Adapted with permission from ref . Copyright 2020 Wiley-VCH.…”
Section: Challenges and Possible Solutions Of Li-rich Mn-based Oxide ...mentioning
confidence: 99%
“…(D) Schematic illustration showing the H 2 O scavenging effect of the MA-C 60 additive and CEI degradation by the attack of HF at the Li-rich CEI. Adapted with permission from ref . Copyright 2020 Wiley-VCH.…”
Section: Challenges and Possible Solutions Of Li-rich Mn-based Oxide ...mentioning
confidence: 99%
“…More importantly, such additives are usually highly effective, resulting in a low dosage (generally below 1 wt%), which can alleviate the cost issue of fullerene-based materials. Recently, Kwak et al [67] reported a novel anti-aging electrolyte additive using malonic acid-decorated fullerene (MA-C 60 , adding 1 wt%) for Li-rich cathodes. The MA-C 60 can not only serve as superoxide dismutase activity to inhibit the solvent decomposition but also has excellent water scavenging capability to sustain a long-term, stable cathode electrolyte interface (Fig.…”
Section: Lithium-ion Batteriesmentioning
confidence: 99%
“…Han et al . [ 117 ] used a Malonic acid‐decorated fullerene (MA‐C60) that was highly efficient in scavenging superoxide radicals and water. The use of additives can effectively avoid superoxide radical catalyzed electrolytes oxygenation, and prevent the reaction of PF 5 with water to generate corrosive HF, as shown in Figure 9C.…”
Section: Optimization Strategiesmentioning
confidence: 99%
“…Copyright 2020, Elsevier B.V. (C) Schematic representation of the degradation of a Li‐rich cathode by reactive species and protection of a Li‐rich cathode by the MA‐C60 additive. Reproduced with permission from Ref [117]. Copyright 2020, WILEY‐VCH.…”
Section: Optimization Strategiesmentioning
confidence: 99%